2013
DOI: 10.1371/journal.pone.0078526
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and Anomalous Hydration of Collagen Fibril under Heating

Abstract: BackgroundType I collagen is the most common protein among higher vertebrates. It forms the basis of fibrous connective tissues (tendon, chord, skin, bones) and ensures mechanical stability and strength of these tissues. It is known, however, that separate triple-helical collagen macromolecules are unstable at physiological temperatures. We want to understand the mechanism of collagen stability at the intermolecular level. To this end, we study the collagen fibril, an intermediate level in the collagen hierarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…The non-equilibrium behaviors of peptide chains have also been observed in native collagen fibril 69, 70 and oxyhemoglobin crystals 71 . When one increase the temperature of native collagen fibril, the measured curves for Young’s modulus and logarithmic decrement are very different for different rates to increase the temperature, i.e.…”
Section: Discussionmentioning
confidence: 80%
“…The non-equilibrium behaviors of peptide chains have also been observed in native collagen fibril 69, 70 and oxyhemoglobin crystals 71 . When one increase the temperature of native collagen fibril, the measured curves for Young’s modulus and logarithmic decrement are very different for different rates to increase the temperature, i.e.…”
Section: Discussionmentioning
confidence: 80%
“…Usually, about 0.3-0.7 kg of unfreezable water remains associated per kilogram of a 'dry' protein [58]. Assuming that the average molar mass of one amino acid in collagen is 0.1 kg mol -1 , a roughly approximation leads to a value of 4 mol of water per moles of amino acid of collagen, which is slightly higher than the value determined by DVS [59] or X-ray diffraction for adsorbed multilayer water in collagen and collagen peptides [60], certainly because of the presence of HA in dermis.…”
Section: Water Quantification and Collagen Denaturationmentioning
confidence: 88%
“…A more plausible explanation for the increased tendon stiffness may lie in changes of the material properties of collagen fibrils. Recent research by Gevorkian and colleagues ( 2009 , 2013 ) has demonstrated that the collagen triple-helix constituting the microfibrils of collagen type I fibers (i.e., the by far most prevalent type of collagen in tendons) is thermally unstable at physiological temperatures. Studying collagenous material obtained from rat Achilles tendons, the authors found the Young’s modulus of collagen fibrils to be higher by ~14 % at 20 °C as compared to 40 °C (Gevorkian et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%